Qualitative research: The essential guide to theory and practice - Savin-Baden, Maggi; Major, Claire Howell (London Routledge, 2025)
The second edition of Qualitative Research is a one-stop resource for all those approaching qualitative research for the first time, as well as those revisiting core concepts and issues. It presents a comprehensive overview of this rapidly developing field of inquiry, cleverly combined with practical, hands-on advice on how to conduct a successful qualitative study.